The Effect of Self-Efficacy and Big Five Personality Traits Towards Entrepreneurial Intention on International Business Management - Saptadjaya, Kevin; Gunawan, Lenny (Universitas Ciputra Surabaya, 2020)
With lesser number of entrepreneurs compared to the neighboring country and other developed countries. Indonesia tries to compete with other countries by increasing their number of entrepreneurs. The fact that the government trying to reduce unemployment, the government need to create more ways for the startup in Indonesia to increase. Recent studies by the government research team shows that the open unemployment rate in Indonesia is actually increasing among the University and Diploma graduates. Universitas Ciputra is one of the entrepreneur-based university in Indonesia that is trying to solve this problem. One way to increase the number of entrepreneurs in Indonesia is by understanding the entrepreneurial intention. The purpose of this study is to examine the effect of self-efficacy and the big five personality traits towards entrepreneurial intention on International Business Management Students – International Class in Universitas Ciputra as a sample of this study. The data collected in this study is using a quantitative method by distributing a questionnaire to the samples, on a standard measurement using a 5- point Likert scale, and processed using IBM SPSS Statistics 20 program. In this study, it has been found that among 6 variables presented: self- efficacy, conscientiousness, openness to experience, extroversion, agreeableness, and neuroticism. Only two variables significantly influence entrepreneurial intention, which is self-efficacy and conscientiousness of the individuals. The results of this study are expected to help broaden the horizon of Entrepreneur-based universities in selecting the new enrolled batch. Keywords: Self-efficacy, Big Five Personality Traits, Entrepreneurial Intention